Review of social issues for large-scale land investment in Zambia - Giles Henley (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Given unsuccessful experiences to date in establishing large-scale investments for biofuels in Zambia, this paper explores the social constraints that may hinder future efforts to use the same models. The author reviews the legal framework that has guided the establishment of most agricultural investments to date (including investment in biofuels), and analyses some of the issues and social repercussions associated with them, through a review of existing case studies. He also explores through light-touch analysis of available cost data the costs associated with carrying out investments in a more socially inclusive way, relying on international best practice. He suggests that, before governments and investors embark on new efforts to expand biofuel production through an approach that involves land transfers, there is a need to strengthen institutional capacity around compensation and resettlement issues in both government and customary authorities and raise investors' awareness of the risks associated with failing to obtain community consent.
Keywords: O13; Q10; 330; biofuels; feedstocks; social constraints; Zambia; resettlement